Animal rights and environmemntal rights in Brazilian Supreme Court - F. C. Xavier (Правоприменение)
The subject. The article analyzes the arguments of the Federal Supreme Court of Brazil, used in the consideration of disputes concerning animal rights, in comparison with the developments of theorists in this field.The purpose of the article is to justify the necessity of respect for the rights of animals and the “animal dignity” by the courts.The methodology includes formal-legal analysis of courts’ decisions, comparative-legal analysis and synthesis as well as formal-logical analysis of scientific researches in the field of animal rights.The main results and scope of application. It is wrong to claim that the Brazilian Supreme Court decision in “Vaquejada” case (or even in “Farra do Boi” or cockfights cases) would be an increase in the process of a supposed recognition of animal rights in the Brazilian constitutional jurisdiction. In such cases, most of the Judges who participated in the trial pondered and reinforced the prevalence of environmental law, including it wildlife protection (and non-submission of the animals to cruelty), pursuant to Art. 225, § 1, VII, of the Brazilian Constitution. In this way, it would have been disregarded the categorical difference between environmental law and animal rights. The Constitution itself encourages confusion between those categories when dealing with the prohibition of animal cruelty in a chapter on the environment (chap. VI). This article argues that the focus on the statement of environmental law, the Supreme Court allows them to be strengthened arguments considered as obstacles to the defenders of animal rights, particularly the anthropocentric argument that the balanced environment is important to make possible to human beings more quality of life. Analyzing the decisions, especially in of Vaquejada and Farra do Boi cases, it appears that points many important analyzed in the theoretical debate about animal rights, such as the notions of “animal dignity” and “flourishing life” are totally neglected. The article uses widely the arguments presented by Martha Nussbaum in her text Beyond “Compassion and humanity”: Justice for Nonhuman Animals, particularly to show that the approach of “capabilities” developed by it can provide a better theoretical orientation of the approaches Kantian contractualism and utilitarianism to the animal rights, mainly because it is able to recognize the breadth of the concept of “animal dignity”. It is considered that the central point to be faced in order to recognize the rights of animals is the one raised by the High Court of Kerala in the case of Nair v. India Union (June 2000), which Nussbaum highlights as the epigraph of the her text: “Therefore, it is not only our fundamental duty to show compassion to our animal friends, but also to recognize and protect their rights [...] If human beings have a right to fundamental rights, why not animals?”.Conclusions. Understanding the prohibition of animal abuse as a measure of environmental protection for the benefit of present and future generations is incorrect and does not take into account the basic principles that form the core of animal rights.Brazilian law will go a long way towards protecting animal rights when (and if) it expressly recognizes that animals (at least some of them) are creatures created for a decent existence”; when, for example, it permits the trial of habeas corpus filed in favour of a bull locked up in a farm or slaughterhouse.